Жанровий склад верхньоприп’ятськихобрядових пісень - Рибак, Ю. (Народна творчість та етнографія, 2005)
Contemporary Ukrainian folkloristic does not have a generalized genre division of the oral poetic and music pieces. Three approaches are use usually for such classification – ethnographical, philological and musical. The nature of such genres requires using the combination of at least two approaches simultaneously. During the last decade the author of this article together with the group of the scholars from the research laboratory of the musical ethnology have done recordings in the Volyn' Region. The goal was to record all the materials on the musical tradition including rites and rituals. The results of this work with the description of the particularities of the musical genres of Upper Prypyat Region are given in this article. The developed genre system of this region shows some individual characteristics which require special approach for analyzing them and this methodic should be based on the grounds of contemporary ethnomusicology and bordering spheres.